Nomads as agents of cultural change : the Mongols and their Eurasian predecessors - Amitai, Reuven; Biran, Michal (Perspectives on the global past., 2015)
Since the first millennium BCE, nomads of Eurasian steppe have played a key role in world history and the development of adjacent sedentary regions. This volume brings together scholars from different disciplines to explore how nomads played the role of 'agents of cultural change.'